Endothelial Function and Arterial Stiffness Relate to Functional Outcomes in Adolescent and Young Adult Fontan Survivors. Issue 9 (24th September 2016) - Goldstein, Bryan H.; Urbina, Elaine M.; Khoury, Philip R.; Gao, Zhiqian; Amos, Michelle A.; Mays, Wayne A.; Redington, Andrew N.; Marino, Bradley S.
Abstract : Background: Fontan survivors demonstrate diminished vascular function and functional outcomes, but the relationships between these measures have not been established. Methods and Results: We performed a cross‐sectional study of 60 Fontan survivors (52% male) with a mean age of 13.9±4.1 years and mean Fontan duration of 9.9±4.2 years. Multimodality assessment of endothelial function (reactive hyperemia index and flow‐mediated dilation) and arterial stiffness (augmentation index and baseline pulse amplitude) was performed with peripheral arterial tonometry and brachial flow‐mediated dilation. Aerobic capacity was determined using cardiopulmonary exercise testing; mean peak and percentage of predicted oxygen consumption (VO2 ) were 27.8±7.6 mL/kg per minute and 71.0±21.2%, respectively. Quality of life and physical activity were assessed using the Pediatric Quality of Life Inventory (PedsQL) and the Physical Activity Questionnaire. Vascular measures served as predictor variables, whereas functional measures served as outcome variables. In all cases, worse vascular measures were associated with worse functional measures. Flow‐mediated dilation–derived reactive hyperemia index ( P <0.05) was positively associated with VO2 at anaerobic threshold. Peripheral arterial tonometry–derived baseline pulse amplitude ( P <0.05) was negatively associated with the ratio of minute ventilation to carbon dioxide at anaerobic threshold. Flow‐mediated dilation–derived reactive hyperemia index and peripheral arterial tonometry–derived augmentation index ( P <0.05) were positively and negatively associated, respectively, with peak VO2 . Maximum flow‐mediated dilation ( P <0.05) was positively associated with Physical Activity Questionnaire score. Peripheral arterial tonometry–derived augmentation index and baseline pulse amplitude ( P <0.05) were negatively associated with parent‐reported PedsQL total and physical heath summary scores. Conclusions: Increased arterial stiffness and decreased endothelial function are associated with lower aerobic capacity, physical activity, and quality of life in adolescent and young adult Fontan survivors. Understanding the cause–effect relationship between vascular function and functional outcomes is an important next step.